Experimental Characterization of a Tri-Axial FBG Accelerometer for Underwater Thruster-Induced Vibration Detection - Muhammad Alif Rahman Sukapraja; Retno Wigajatri Purnamaningsih; Sasono Rahardjo; Maristya Rahmadiansyah; Tinova Pramudya (International Journal of Electrical, Computer, and Biomedical Engineering, 2026)
This paper presents an experimental engineering validation of a tri-axial Fiber Bragg Grating (FBG) accelerometer for detecting thruster-induced vibrations in submerged environments. The sensor integrates three orthogonally arranged FBG elements within a compact, waterproof housing, enabling vibration measurements along three spatial directions. Experiments were conducted using a DC thruster as a repeatable vibration source under both free-air and underwater conditions. Comparative results show a marked increase in Bragg wavelength shift (ΔλB) when submerged, with peak-to-peak variations reaching approximately 0.0267 nm on non-primary axes and up to 0.1005 nm on the axis aligned with the excitation, compared to approximately 0.0044 nm in free air. Sensor sensitivity, repeatability, and hysteresis were evaluated through cyclic loading-unloading tests. The maximum hysteresis observed was 0.0053 nm, corresponding to approximately 5% of the full-scale wavelength shift, indicating stable and predominantly elastic behavior.